ANALISIS PENGARUH KEMAMPUAN, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI ACCOUNT REPRESENTATIVE PADA KPP PRATAMA JAKARTA PENJARINGAN - Rinto Ariyanto, - (2011)
The Tax Office for Primary of Jakarta Penjaringan has its vision to be a model of public service which conducts a world class taxation system and management with public trust and pride. To implement the task, it requires good Account Representative with good work performance. Work competency, work motivation, work satisfaction are three factors highlighted as a tendency in increasing official performance. This research studies a significance of influency among three independent variables, such a work competency (X1), work motivation (X2), work satisfaction (X3) toward the dependent variable or work performance (Y). Instrument of research used is questionnaire, by quantifying data with Liker! scale 1 to 5. Validity and reability tests are conduscted on 30 respondents where as the analysis technique uses regression model with 30 people representing sample of population based on Slovin formulae. The regression equation is Y = 14,591+ 0,652X1 + 0,144X2 + 0.057X3 indicating all variables contributes positive influence. In partial regression, Fcoun1 > Ftable (6, 116. >2, 975) shows that the three independent variables simultaneously contribute positive and significant influence. It is suggested to the policy makers to take more concerns on work satisfaction by giving better and more proportional compensation, more conductive environment to motivate the official in attempt to achieve higher performance